Mechanisms for implementing Lean - technologies as an innovative approach in modeling the structure of the standard time determining for construction processes implementation - Rudnieva, I. (Ways to Improve Construction Efficiency, 2021)
Recently, a significant number of scientists’ works have been devoted to the application of the lean-production principles, in particular, the introduction of lean construction. Objective construction cost estimation is a key factor in construction projects. The article discusses the problems, significant losses, low productivity in construction companies and the possibilities of their elimination due to the use of the lean-construction management concept as an innovative approach in modeling the structure of the standard time determining for construction processes implementation in order to increase the company’s competitiveness. The productivity of the construction industry worldwide has been falling for the past 40 years. Companies must use appropriate methods to reduce their losses and increase productivity levels so that they can stand in the rapidly changing competitive environment of the current business environment. One of the approaches to improving the situation is the use of "lean management" in the construction industry is the result of the desire of construction business owners to optimize costs and increase labor productivity, the efficiency of organizational and technological processes, and introduce lean- production in the construction industry. A huge number of scientists and construction professionals are trying to change the traditional organizational and technological form of construction production and add value to owners, while making real profits. As a result, lean manufacturing tools have emerged that have been successfully applied to simple and complex construction projects. Ukraine is very far behind in terms of the development level of innovative processes from many countries of the world. Outdated ENiR norms, which were developed without taking into account the Lean strategy, need to be finalized. Of course, the introduction of a lean manufacturing system is a topic for the near future. Thanks to this, it is possible to significantly reduce the cost overruns on projects, as well as the time of their implementation up to 30%, or even more. Therefore, future research objective should be the development of a new modern methodology for determining the standard time, which will take into account the criteria of lean technologies, as an innovative approach in modeling the structure and sequence of all operations of construction processes.